Reformasi Birokrasi Melalui SOP Layanan Pengaduan Berdasarkan Prinsip-Prinsip Good Governance dI Disdikbud Kota Samarinda - Muhamad Candra Aji Saputro; Siti Nur Halizah; Bahrian Bahrian; Julio Virera Ladiawa; Subagio Subagio; Siti Nor Aleyda; Cindy Irmadani; Enos Paselle (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Bureaucracy is an administrative system in an organization that has the function of administering government and serving the community by carrying out daily tasks in a structured manner in a clear hierarchy. Bureaucratic reform is carried out in order to realize good governance.. Implementing Good Governance is one of the goals in improving government governance, which is the public's demand for the management of public sector organizations. In implementing the SOP for Complaints Services at the Samarinda City Education and Culture Office, there are several problems such as differences in understanding and variations in the format of the SOP documents produced, and there are even regional organizations that have not implemented this regulation. This research aims to describe the realization of bureaucratic reform through Complaint Service SOPs based on the principles of Good Governance in the Samarinda City Education and Culture Office. The research method used in this research is descriptive qualitative with data collection techniques through interviews and observation. The data analysis technique is carried out with the data obtained and then written in the form of a detailed report, then the report will be focused according to the problem formulation, as well as drawing conclusions. The results of the research show that the Samarinda City Education and Culture Office has demonstrated a significant commitment to improving public services through the implementation of the Complaint Service SOP. Concrete steps such as transparency through the official website, accountability in responding to and resolving complaints, as well as efforts to maintain legal certainty are positive things that have been taken to support bureaucratic reform.